Human resource management, employee engagement, and nonprofit hospital performance - Johansen, Morgen S.; Sowa, Jessica E. (Nonprofit management & leadership, 2019)
Human resource management (HRM) has been shown to impact organizational performance, but more research is needed on particular human resource (HR) practices in nonprofits and their effect on performance. In this article, we explore one HRM practice argued to influence performance, employee engagement in decision‐making, examining whether involving staff at different levels of a nonprofit affects nonprofit organizational performance. Drawing on data from a 2011 study of nonprofit hospitals, we find employee engagement has a positive influence on managerial and stakeholder perceptions of organizational performance. Employee engagement in decision‐making is also related to objective nonprofit performance measures, although the effects are less consistent. We conclude by discussing the implications of these findings for nonprofit research and practice.